A new species of Ptychognathus Stimpson, 1858, from East and Southeast Asia, previously identified as Ptychognathus barbatus (A. Milne-Edwards, 1873) (Crustacea, Decapoda, Brachyura, Varunidae) - Jhih-Wei Hsu; Jose Christopher E. Mendoza; Hsi-Te Shih (ZooKeys)
The brackish-water crabs of the genus Ptychognathus Stimpson, 1858, currently the most diverse genus within the family Varunidae, typically inhabit estuaries or seashores influenced by freshwater. Among the species in this genus, a commonly recorded species identified as Ptychognathus barbatus (A. Milne-Edwards, 1873) has been recorded across the western Pacific, including Japan, Taiwan, China, the Philippines, Malaysia, Indonesia, and New Caledonia (type locality). However, some previous studies suggested that most of these records do not represent the true P. barbatus. The present study reexamines these records and specimens and describes a new species, P. dajie sp. nov., from East and Southeast Asia, based on morphological differences and genetic data from mitochondrial cytochrome c oxidase subunit 1 (COI). This new species is similar to its congeners but can be distinguished by the features of the carapace, the setation of ambulatory legs, and male first gonopods. In addition, the intraspecific distances of P. dajie sp. nov. are below 0.77%, while the interspecific distances between this new species and other species are larger than 11.89%.